Rituximab Hypersensitivity: From Clinical Presentation to Management - Fouda, Ghada E.; Bavbek, Sevim (Frontiers in Pharmacology, 2020)
Rituximab is a chimeric monoclonal antibody (mAbs) against CD20 molecule which is expressed on human B cells. It has been used for the treatment of various lymphoid malignancies, lymphoproliferative diseases and rheumatologic disorders. Rituximab is generally well tolerated. However, increased use of rituximab has been associated with hypersensitivity reactions (HSRs), which can be classified as infusion-related, cytokine-release, type I (IgE/non-IgE), mixed, type III, and type IV reactions. Immediate infusion-related reactions to rituximab are quite common and decrease in frequency with subsequent infusions. However, in about 10% of patients, severe infusion-related reactions develop, which prevent its use. Some of immediate infusion reactions are due to a cytokine-release but some reactions raise concerns for type I (IgE/non-IgE) hypersensitivity. Recent studies have shown the presence of serum anti-rituximab antibodies, either represented by the IgG or IgE isotype. In some cases, clinical manifestations of IgE-mediated reactions and cytokine-release reactions partially overlap, which is called a mixed reaction. Classified as Type III reaction, rituximab-induced serum sickness reactions have been reported in patients with autoimmune diseases and hematological malignancies. The classic serum sickness triad (fever, rash, and arthralgia) has been observed in patients mainly with an underlying rheumatologic condition. Severe delayed type IV hypersensitivity reactions including non-severe maculopapular rash to severe reactions such as Stevens-Johnson syndrome and toxic epidermal necrolysis have been rarely reported following rituximab injection. Comprehensive reviews focused on rituximab-induced HSRs are scarce. We aimed to review clinical presentations, underlying mechanisms of rituximab hypersensitivity, as well as management including rapid drug desensitization.